STUDI LITERATURE INVENTARISASI TUMBUHAN OBAT KHAS KABUPATEN PASANGKAYU - Jamal, Jamaluddin; Arifin, Pitriani; Diana, Khusnul; Anjelita, Anjelita; Parumpu, Firdawati A (Preventif : Jurnal Kesehatan Masyarakat, 2023)
Inventory of medical plants is an activity of collecting and compiling data and facts regarding natural resources for resource management planning and can be used as database to reveal potential and information as a reference for introducing plant species in the research area. This study aims to make an inventory of what plants are efficacious as drugs, and to find out their benefits based on preclinical and clinical trials. This type of research is a descriptive study using the SLR (Systematic Literature Review) method with a sample of 21 literatures. The results of the library show that there are 68 plants that are used empirically by the Kabupaten Pasangkayu community. Some of these plants have gone through preclinical and clinical trials. Plants that are efficacious as traditional medicine vary, such as antidiabetic, antihypertensive and so on empirically amounted to 68 plants which from 4 different regions that was pasangkayu 57 plants, mamuju 5 plants, dapurang 3 plants and baras 3 plants.